POD04 Analysis of eight rating scales supports the use of functional outcome measures in prion disease clinical trials: experience from the PRION-1 trial and the National Prion Monitoring cohort. Issue 11 (22nd October 2010) - Thompson, A; Rudge, P; Wroe, S; Mead, S; Darbyshire, J; MacKay, A; Ranopa, M; Collinge, J; Gopalakrishnan, G; Walker, S
Abstract : PRION-1, the largest clinical trial in prion disease to date, showed no effect of the experimental therapeutic quinacrine on survival. Here we report analyses showing that quinacrine had no demonstrable benefit (p>0.4) when assessed by a range of rating scales. These included neurocognitive (Mini-Mental State Examination, ADAScog), psychiatric (Brief Psychiatric Rating Scale), global (Rankin and Global Impression of Change), clinician-rated (Clinician's Dementia Rating (CDR)) and functional (Barthel) scales. These rating scales have several potential benefits over survival as an outcome measure: here we assess their validity and performance over 77 person-years follow-up in 101 symptomatic patients in PRION-1. Overall, across a range of models applied, we found that the Barthel and CDR scales were most robust to the difficulties posed by a prion disease clinical trial. A combination of selected subcomponents from these two scales gave increased power to detect clinically relevant effects in a future clinical trial of feasible size, compared to use of survival alone. We also discuss our work refining the use of these scales in the National Prion Monitoring Cohort, an ongoing prospective observational study of all types of human prion disease in the UK, and how this will inform the planning of future therapeutic trials.